Corrosion Inhibition of Mild Steel in Acidic Media by Expired Carbimazole Drug - Al-abbasi, Aisha; Shana, Ibrahim E. (Journal of Pure & Applied Sciences, 2021)
ABSTRACT The efficiency of the anti-thyroid, Carbimazole, expired drug, (CD), as corrosion inhibitor for mild steel in 0.5MHCl was investigated by weight loss method. Data obtained from weight loss measurement were analysed, and the results show that, the used Carbimazole drug was a good inhibitor. The inhibition efficiency increases with increasing the concentration of CD inhibitor and reached a maximum value of 84.95% at 30 OC and 100 ppm of the used inhibitor. The adsorption isotherm of CD obeyed Langmuir adsorption isotherm. Quantum chemical calculations based on density function theory, DFT, were performed on CD drug. Calculated parameters such as the highest occupied molecular orbital energy (EHOMO), the lowest unoccupied molecular orbital energy (ELUMO), energy gap (ΔE), dipole moment (µ), electronegativity (), electron affinity (A), global hardness (η), softness (σ) and ionization potential (I), were calculated and correlated to the experimental data.